Peer-To-Peer Recognition of Learning in Open Education - Schmidt, Jan Philipp; Geith, Christine; Håklev, Stian; Thierstein, Joel (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2009)
Recognition in education is the acknowledgment of learning achievements. Accreditation is certification of such recognition by an institution, an organization, a government, a community, etc. There are a number of assessment methods by which learning can be evaluated (exam, practicum, etc.) for the purpose of recognition and accreditation, and there are a number of different purposes for the accreditation itself (i.e., job, social recognition, membership in a group, etc). As our world moves from an industrial to a knowledge society, new skills are needed. Social web technologies offer opportunities for learning, which build these skills and allow new ways to assess them. This paper makes the case for a peer-based method of assessment and recognition as a feasible option for accreditation purposes. The peer-based method would leverage online communities and tools, for example digital portfolios, digital trails, and aggregations of individual opinions and ratings into a reliable assessment of quality. Recognition by peers can have a similar function as formal accreditation, and pathways to turn peer recognition into formal credits are outlined. The authors conclude by presenting an open education assessment and accreditation scenario, which draws upon the attributes of open source software communities: trust, relevance, scalability, and transparency.